EKSISTENSI PEREMPUAN MODEREN DALAM NOVEL KENANGA KARYA OKA RUSMINI - Ambarini Asriningsari; Ngatmini . (Sasindo, 2013)
This reseacrh entitled ?óÔé¼?ôExiztence of Modern Female in the Kenanga Novel by Oka Rusmini. The problems of this research are How does the famale position in male culture of Kenanga Novel by Oka Rusmini and How does existence of modern woman in Kenanga Novel by Oka Rusmini? The aims to be reached are to describe modern woman position in male culture in the Kenanga by Oka Rusmini and to describe modern female existance in the Kenanga Novel by Oka Rusmini. The methode used for analyze the problems and reach the aims is methods of sociology of literature. This methods is consider some sociall aspect. Beside that, this research also used qualitative methods which choosen based on male culture as research object data as appropriate soft data to use that qualitative methods. Based on the analysis that have found, modern female existence in the Kenanga Novel by Oka Rusmini could seen thourgh characters observation on the strength explicit qualtivication, extern qualification, and functional qualtification. Based on those three qualitication, statment that altough the female was live at powerful Bali culture, modern female in the novel are independent and does not depend on male, has found. Kenanga has to keep studying. Noone can control her life when she was studying deeply because knowledge is the only where her hope and her dream fallen. She feel save by mastered the knowledge. At least, Kenanga has something for being respected and honor by her mind, not because she was accidently be born as wealthy Brahmana female. That is indicated the modern female existence. Keyword: existence, female, modern